2017
DOI: 10.1162/asep_a_00519
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Domestic Institutions and FDI on Innovation—Evidence from Chinese Firms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This study revealed that formal institutions significantly contribute to the banks’ capital-raising strategy, survival and sustainability in developing economies. In line with existing literature that revealed that firms, in most cases, rely on the institution for acceptance, resources and strategies development (Greenman, 2013; Jain and Sharma, 2013; Qu and Wei, 2017); the findings of this study show that BoG, as one of the bank’s external government institutional environment and regulator, plays an essential role in the strategy adoption implementation and financial capacity of the banks.…”
Section: Discussion Theoretical Implication Recommendation and Conclu...supporting
confidence: 89%
“…This study revealed that formal institutions significantly contribute to the banks’ capital-raising strategy, survival and sustainability in developing economies. In line with existing literature that revealed that firms, in most cases, rely on the institution for acceptance, resources and strategies development (Greenman, 2013; Jain and Sharma, 2013; Qu and Wei, 2017); the findings of this study show that BoG, as one of the bank’s external government institutional environment and regulator, plays an essential role in the strategy adoption implementation and financial capacity of the banks.…”
Section: Discussion Theoretical Implication Recommendation and Conclu...supporting
confidence: 89%
“…Some of the studies found that FDI encourages a firm's or country's innovation capacity, as seen in Ustalar and Sanlisoy [65], Nyeadi and Adjasi [52], Ismail [66], Dhrifi [58], Erdal and Gocer [59], Zhang [60], Girma et al [51], Zeng and Zhou [12], Kemeny [61], Wang et al [53], Osano and Koine [57], Shamsub [67], Khachoo and Sharma [54], Sivalogathasan and Wu [54], Keller and Yeaple [55], Caves [47], Globerman [68], Blomstrom and Persson [69], and Javorick [46], while others revealed FDI has negligible or insignificant effects on innovation. These include Garcia et al [56], Chen [63], Aitken and Harrison [70], Haddad and Harisson [71], Djankov and Hoekman [72], Sasidharan [73], Qu and Wei [74], Dunning and Lundan [48], and Mohamed et al [64]. Table 1 shows the firm/industry-level studies, and Table 2 presents country-level studies.…”
Section: Theoretical Foundation and Literature Reviewmentioning
confidence: 99%
“…Institutional considerations are regarded as an important determinant of economic growth in Vietnam (Bon Van, 2019). While government support including the protection of intellectual property rights are positively linked to both FDI and innovation (Egan, 2013; Qu and Wei, 2017), promoting institutional quality is important in attracting FDI and promoting local innovation. Given that institutions are believed to perform better in those Vietnamese provinces with industrial zones, our finding is consistent with earlier work (Meyer and Nguyen, 2005) insofar as industrial parks are found to have a significant role in attracting FDI.…”
Section: Discussionmentioning
confidence: 99%